Perception of 3D Slant Out of the Box - Van Der Kooij, Katinka; te Pas, Susan F. (Frontiers in Psychology, 2011)
Evidence for contextual effects is widespread in visual perception. Although this suggests that contextual effects are the result of an inherent property of the visual system, current explanations are limited to the domain in which they occur. In this paper we propose a more general mechanism of global influences on the perception of slant. We review empirical data and evaluate proposed explanations of contextual biases. By assessing not only a model about 3D slant perception but also evaluating more generic mechanisms of contextual modulation, we show that surround suppression of neural responses explains the major phenomena in the empirical data on contextual biases. Moreover, contextual biases may be part of a mechanism of grouping and segmentation.